Quality of life in cancer survivors: an integrative review - Pinto, Bruna Knob; Lima, Julyane Felipette; Muniz, Rosani Manfrin; Schwartz, Eda (Rev Rene, 2013)
This study aims at identifying factors related to the quality of life of cancer survivors. The databases PubMed, LILACS and SciELO were used, being quality of life, survival and neoplasms the main keywords entered. Sixty-eight articles were found and ten that approached aspects related to quality of life of cancer survivors were selected. The results analysis was performed in stages. Several factors were identified and grouped into physical (chewing, pain and others), psychological (disease conception), social, financial (high cost of treatment) and miscellaneous (age, treatment performance among others). It is believed that the analysis of the different areas that comprise the quality of life of patients can assist health professionals in the implementation of assistance practices that consider the multidimensionality of cancer survival. DOI:https://doi.org/10.15253/2175-6783.20130004000020